The Influence Of Liquidity, Company Growth And Capital Structure On Company Value With Profitability As A Moderating Variable In Property & Real Estate Companies Listed On The Indonesia Stock Exchange In 2019 – 2023 - Muhammad Akbar Ramadhan; Yana Hendayana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to analyze the effect of liquidity, company growth, and capital structure on firm value with profitability as a moderating variable in Property and Real Estate companies listed on the Indonesia Stock Exchange in 2019 - 2023. The research method uses MRA (Moderated Regression Analysis) with quantitative data processed through the application Eviews13 software. The results of this study indicate that Liquidity has a significant positive effect on Company Value. Company Growth does not affect Company Value. Capital Structure has a significant positive effect on Company Value. Profitability cannot moderate the effect of Liquidity on Company Value. Profitability cannot moderate the effect of Growth on Company Value. Profitability can moderate the effect of Capital Structure on Company Value. The implications of this research are that investors are expected to be more careful in choosing stocks to invest in, in addition, management can create strong financial stability, can implement an effective asset management system to manage assets optimally, can consider the optimal balance between debt and equity, and can identify and reduce inefficient costs.